80.0k views
3 votes
What is the solution of the equation?

What is the solution of the equation?-example-1

2 Answers

3 votes


√(2x - 5) = x - 4

2x - 5 = (x - 4) {}^(2)

2x - 5 = x {}^(2) - 8x + 16

x {}^(2) - 10x + 21 = 0

(x - 3)(x - 7) = 0

x = 3 \\ x = 7
User Adesurirey
by
5.9k points
5 votes

Answer: 7

Explanation:


√(2x-5)+4 = x


√(2x-5) = x-4 subtracted 4 from both sides


(√(2x-5))^2 = (x-4)^2 squared both sides to eliminate square root

2x - 5 = x² - 8x + 16 expanded right side

0 = x² - 10x + 21 subtracted 2x and added 5 on both sides

0 = (x - 3) (x - 7) factored right side

0 = x - 3 0 = x - 7 applied zero product property

x = 3 x = 7 solved for x

Check:

x = 3


√(2(3)-5)+4 = (3)


√(1)+4 = 3

1 + 4 = 3

FALSE! x = 3 is NOT a valid solution


x = 7


√(2(7)-5)+4 = (7)


√(9)+4 = 7

3 + 4 = 7

TRUE! x = 7 IS a valid solution

User ChuckKelly
by
6.4k points